2021
DOI: 10.3389/fimmu.2020.621222
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Systemic Inflammation in Patients With Severe Burn Injury Is Accompanied by Influx of Immature Neutrophils and Shifts in T Cell Subsets and Cytokine Profiles

Abstract: Severe burn injury causes local and systemic immune responses that can persist up to months, and can lead to systemic inflammatory response syndrome, organ damage and long-term sequalae such as hypertrophic scarring. To prevent these pathological conditions, a better understanding of the underlying mechanisms is essential. In this longitudinal study, we analyzed the temporal peripheral blood immune profile of 20 burn wound patients admitted to the intensive care by flow cytometry and secretome profiling, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 73 publications
5
55
2
Order By: Relevance
“…Emergency granulopoiesis, which has been extensively described following traumatic injury and microbial challenge [27,28], is a part of the first line of cellular defense that crucially modulate subsequent repair processes after tissue damage [29]. However, on the other hand, an exaggerated release of neutrophils leads to bone marrow exhaustion and in turn, can impair the innate immune response to secondary hit such as surgery or infection [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Emergency granulopoiesis, which has been extensively described following traumatic injury and microbial challenge [27,28], is a part of the first line of cellular defense that crucially modulate subsequent repair processes after tissue damage [29]. However, on the other hand, an exaggerated release of neutrophils leads to bone marrow exhaustion and in turn, can impair the innate immune response to secondary hit such as surgery or infection [21].…”
Section: Discussionmentioning
confidence: 99%
“…Further, we observed a massive presence of immature (CD16 dim CD62L bright ) neutrophils in severely injured patients, whereas healthy individuals lack this population. It is assumed that immature neutrophils have impaired functional ability [21]. Moreover, Spijkerman et al have shown that the ratio of immature neutrophils positively correlates with the severity of the injury and the development of infectious complication [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Burn injury results in a robust systemic activation of both innate and adaptive immunity 14 . Murine burn injury acutely increases relative and absolute numbers of neutrophils 15 , induces acute activation and increase in numbers of Regulatory T cells 15 , 16 and impairs CD4 and CD8 T cell function 17 . Neutrophils are a key cellular component for the resolution of the injury as they are first recruited to the site of injury in quantitatively high numbers 18 .…”
Section: Introductionmentioning
confidence: 99%